Answer:
(5,-1)
Step-by-step explanation:
4x+3y=17
3x+2y=13
So elimination sounds fun but we will have to do manipulation:
Multiply top equation by 2 and bottom equation by 3. This will cause the second term in both by 6y which means we would be setup for elimination.
8x+6y=34
9x+6y=39
--------------------now subtract the equations
-x+0=-5
So x=5
Now plug it into either question (no matter which-pick and choose)
I will go with the second original 3x+2y=13
So if x=5 we have 15+2y=13
Subtract 15 on both sides: 2y=-2
Now divide both sides by 2: y=-1
Answer (5,-1)
It factors to (x+12)(x-12)
This is the same as (x-12)(x+12) as we can multiply two expressions in any order we want. This is like saying 7*5 is the same as 5*7
I used the difference of squares rule to factor x^2 - 144. It might help to write x^2 - 144 as x^2 - 12^2, then compare it to a^2 - b^2 = (a-b)(a+b)
the answer would be= -2fx+3x^2+15+a/fx
5u + 3v + 6u - v = ?